Comparison of the effects of three hangboard strength and endurance training programs on grip endurance in sport climbers - López-Rivera, E.; González-Badillo, J. J. (Journal of Human Kinetics, 2019)
Intermittent isometric endurance of the forearm flexors is a determinant factor of sport climbing performance. However, little is known about the best method to improve grip endurance in sport climbing regarding maximal or intermittent dead-hang training methods. The aim of this study was to compare the effects of three 8-week finger training programs using dead-hangs (maximal, intermittent, and a combination) on grip endurance. Twenty-six advanced sport climbers (7c+/8a mean climbing ability) were randomly distributed among three groups: maximal dead-hangs with maximal added weight on an 18 mm edge followed by MaxHangs on minimal edge depth; intermittent dead-hangs using the minimal edge depth, and a combination of both. The grip endurance gains and effect size were 34% and 0.6, respectively, for the group following maximal dead-hang training, 45% and 1, respectively, for the group following intermittent dead-hang training, and 7% and 0.1, respectively, for the group applying the combination of both training methods. Grip endurance increased significantly after 4 weeks in the group performing intermittent dead-hangs (p = 0.004) and after 8 weeks in both groups performing intermittent dead-hangs (p = 0.002) and MaxHangs (p = 0.010). The results suggest that the intermittent dead-hangs training method seems to be more effective for grip endurance development after eight week application in advanced sport-climbers. However, both methods, maximal and intermittent dead-hangs, could be alternated for longer training periods